Cruelty or humanity : challenges, opportunities and responsibilities / Stuart Rees. - Rees, Stuart (Policy Press, 2020)
Cruelty has long been a feature of states' domestic and foreign policies but is seldom acknowledged. Governments mouth respect for human rights yet promote discrimination, violence and suppression of critics. Documenting case studies from around the world, distinguished academic and human rights activist Stuart Rees exposes politicians' cruel motives and the resulting outcomes. Using his first-hand observations and insights from international poets, he argues for courageous action to support non-violence in every aspect of public and private life for the survival of people, animals and the planet.